Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69130
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Levels are High at the Combustor-Turbine Interface

Abstract: Turbulence measurements are made in a novel gas turbine rig facility recently used to study combustor-turbine interactions in jet engines [1]. The rig is capable of numerous area traverses surrounding engine turbine nozzle guide vanes (NGVs). The rig is unique in that complete engine hardware of the annular combustion subsystem is used to simulate the upstream flow entering the turbine. The rig operates at cold, near-atmospheric conditions. The turbulence measurements include both the turbulence intensities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…At this stage it should be pointed out that this geometry represents a perspex rig constructed at Loughborough University, similar to that presented by Cha et al [33] and is representative of a combustion module for a large civil engine.…”
Section: Combustor Case Study Descriptionmentioning
confidence: 99%
“…At this stage it should be pointed out that this geometry represents a perspex rig constructed at Loughborough University, similar to that presented by Cha et al [33] and is representative of a combustion module for a large civil engine.…”
Section: Combustor Case Study Descriptionmentioning
confidence: 99%
“…Each steady RANS turbulence model predicted different temperature profiles at the turbine inlet plane and underpredicted jet mixing as well as lateral spreading. Cha et al [5] noted that higher-fidelity modeling (largeeddy simulation) more accurately predicted the turbulence intensities found at the combustor-turbine interface in their experiment. Simply modeling the combustor and turbine together may not be enough to ensure accurate results; higher-fidelity unsteady models are needed to accurately predict the large turbulent structures stemming from the unsteady combustor flowfield.…”
Section: Relevant Literaturementioning
confidence: 93%
“…These results vary with dilution jet arrangement, hole size, hole location, and momentum flux ratio. Cha et al [5] found turbulence levels at the combustor-turbine interface of approximately 35% and length scales of up to 25% of the vane chord length. Vakil and Thole [6] used a nonreacting cold-flow combustor with both dilution and film cooling holes that had measured turbulence levels of 20%.…”
Section: Relevant Literaturementioning
confidence: 99%
“…1 представлены данные математического моделирования не-стационарного вязкого течения, полученные методом прямого численного моделирования (DNS -Direct Numerical Simulation) [11].…”
unclassified
“…В качестве примера регулярной пульсации скорости (давления) потока в ступени турбины на рис. 2 представлено изменение скорости и давления в фазовых координатах (скорость-давление), полученное в результате математического моделирования статор-ротор-взаимо-действия на конкретной турбине [11]. Здесь каждой точке графика соответствует свой момент времени, который не отражен на рисунке, чтобы не загромождать его.…”
unclassified